Practitioner Research in Early Childhood Education and Care: A 21-Year Review of the Literature. Issue 4 (October 2016) - Shannon, Darbianne; Smith, Sara; Dana, Nancy
Abstract : Practitioner research has the potential to facilitate the ongoing knowledge and skill development of preservice and in-service early childhood education and care teachers. The purpose of this systematic literature review is to describe the landscape of practitioner research conducted in the United States. This study synthesizes more than 20 years of practitioner research conducted by practitioners in the "birth to five" context. Critical components that help understand (a) who engages in practitioner research, (b) under what structural conditions practitioner research occurs, and (c) how practitioner researchers actively query their context and collect and analyze data are described. Following the review of the literature, a summary of what is known and implications for expanded understanding are discussed.